Persepsi Mahasiswa Program Pendidikan Profesi Guru (PPG) Pendidikan Sejarah Terhadap Program PPG - Aditya Galih; Corry Iriani (Jurnal Pendidikan Sejarah, 2018)
This research aims to obtain empirical data about the perception of PPG program students of historical education on PPG program. This research was conducted from December 2015 until February 2016. The research method used is descriptive method with survey technique. The sampling technique used in this study is the sampling 'aim' (purposive sampling). The affordable population in this research is the students of PPG program of class III education that is 22 students. Data collection techniques used questionnaires analyzed descriptively using frequency tables and percentages. The result of the research revealed that 65.46% of respondents know that PPG program is a means to obtain educator certificate. This is reinforced by 93.96% of respondents already set to follow the PPG program as the teacher certification path when graduating from college. At the time of the PPG program, 55.85% of respondents already understand the process of PPG program implementation. Understanding of PPG program implementation process is evidenced by 71.23% of respondents know and understand the purpose of certification in the PPG program. The PPG program is perceived by 80.7% of respondents as the right program to produce qualified and qualified teachers supported by effective lecture activities, so the PPG program becomes a recommendation for scholars of history education in particular to follow this program. The conclusion of this research is the PPG program which is followed by providing many new sciences in the scope of pedagogic and professional competence. Providing a certificate of educator after graduating PPG program can support the profession as a teacher. Implementation of PPG program has been running well and on time, although there are still some complaints of students of PPG program class III. Penelitian ini bertujuan untuk memperoleh data empiris mengenai persepsi mahasiswa program PPG pendidikan sejarah terhadap program PPG. Penelitian ini dilaksanakan dari bulan Desember 2015 sampai Februari 2016. Metode penelitian yang digunakan adalah metode deskriptif dengan teknik survai. Teknik pengambilan sampel yang digunakan dalam penelitian ini adalah sampling ‘bertujuan’ (purposive sampling). Populasi terjangkau dalam penelitian ini adalah mahasiswa program PPG pendidikan sejarah angkatan III yaitu sebanyak 22 mahasiswa. Berdasarkan jumlah dari populasi terjangkau yang termasuk sedikit, maka populasi terjangkau ini dijadikan sampel dalam penelitian ini. Teknik pengumpulan data menggunakan angket yang dianalisis secara deskriptif dengan menggunakan tabel frekuensi dan persentase. Hasil penelitian diketahui 65,46% responden mengetahui program PPG adalah sarana untuk memperoleh sertifikat pendidik. Hal ini diperkuat dengan 93,96% responden sudah menetapkan akan mengikuti program PPG sebagai jalur sertifikasi guru saat lulus kuliah. Pada saat perkuliahan program PPG, 55,85% responden sudah memahami proses penyelenggaraan program PPG. Pemahaman tentang proses penyelenggaraan program PPG ini dibuktikan dengan 71,23% responden mengetahui dan memahami tujuan dari sertifikasi yang ada dalam program PPG. Program PPG dipersepsikan oleh 80,7% responden sebagai program yang tepat untuk menghasilkan guru yang berkualitas dan bermutu ditunjang dengan kegiatan perkuliahan yang efektif, sehingga program PPG menjadi rekomendasi bagi sarjana pendidikan sejarah pada khususnya untuk mengikuti program ini. Kesimpulan penelitian ini adalah program PPG yang diikuti memberikan banyak ilmu yang baru dalam lingkup kompetensi pedagogik dan profesional. Pemberian sertifikat pendidik setelah lulus program PPG dapat menunjang profesi sebagai guru. Pelaksanaan program PPG sudah berjalan dengan baik dan tepat waktu, walaupun masih terdapat beberapa keluhan mahasiswa program PPG angkatan III.